Perencanaan Pembinaan Kedisiplinan Berpakaian Peserta Didik di SMP Negeri 7 Pariaman - Rike Fitriani; Indah Muliati (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
This study aims to determine how the planning of student dress discipline development at SMP Negeri 7 Pariaman. This study uses a qualitative method. The subjects of this study consisted of the principal, deputy head of student affairs, homeroom teachers, counseling guidance teachers and students. Data collection instruments used in the form of observation, interviews, and documentation. The results show that the planning for developing student dress discipline at SMP Negeri 7 Pariaman found three things that must be done, including: by socializing the importance of dress discipline, increasing coordination between school principals and educators and collaborating with parents of students